The operational readiness factor of satellite communication networks - T. E. Gelfman; A. P. Pirkhavka (Российский технологический журнал)
Objectives. The most important distinguishing feature of satellite communication networks (SCNs) is topology, which consolidates the scheme for combining nodes and communication channels into a single structure and largely determines the main characteristics of communication systems. The following topologies are used in SCNs: fully connected, tree-like, ring-shaped, and radial (“star” type). The topology can be changed depending on the tasks being solved; for example, to ensure high reliability rates. The most frequently used indicator characterizing the reliability of communication networks is the readiness factor. Considering the SCN as a complex recoverable system, it is advisable to analyze the operational readiness factor along with the readiness factor. This paper investigates the influence of the network topology on the reliability of the SCN.Methods. Queuing theory was used to analyze the flow of events, that is, the flow of failures and recoveries.Results. Assuming that the exponential Mean Time Between Failures (MTBF) model can be used for a central node with a radial network topology, the time dependences of the operational readiness factor were obtained. The reliability of networks with ring and radial topology was compared in terms of the operational readiness factor.Conclusions. To achieve a higher reliability, it is necessary to use an SCN with a radial structure. For example, on a time interval of 12000 h, the operational readiness factor of a two-node SCN with a radial structure is 0.9, and for an SCN with a ring topology with the number of nodes 2, 3, 4, it is 0.7, 0.59, and 0.5, respectively. The study also showed that radial topology is more efficient even with less reliable nodes, that is, with higher failure rates. The advantage of a radial network topology increases as the number of nodes increases. However, in an SCN with a radial topology, failure of the central unit leads to complete degradation of the entire system.